Glu20Ter Variant in PLEC 1f Isoform Causes Limb-Girdle Muscle Dystrophy with Lung Injury - Deev, Roman V.; Bardakov, Sergei N.; Mavlikeev, Mikhail O.; Yakovlev, Ivan A.; Umakhanova, Zoya R.; Akhmedova, Patimat G.; Magomedova, Raisat M.; Chekmaryeva, Irina A.; Dalgatov, Gimat D.; Isaev, Artur A. (Frontiers in Neurology, 2017)
Plectinopathies are orphan diseases caused by PLEC gene mutations. PLEC is encoding the protein plectin, playing a role in linking cytoskeleton components in various tissues. In this study, we describe the clinical case of a 26-year- old patient with an early-onset plectinopathy variant “limb-girdle muscle dystrophy type 2Q”, report histopathological and ultrastructural findings in m. vastus lateralis biopsy and a novel homozygous likely pathogenic variant (NM_201378.3:c.58G>T, NP_958780.1:p.Glu20Ter) in isoform 1f of the gene PLEC. The patient had an early childhood onset with retarded physical development, moderate weakness in pelvic girdle muscles, progressive weakening of limb-girdle muscles after the age of 21, pronounced atrophy of axial muscles, and hypertrophy of the gastrocnemius, deltoid, and triceps muscles, intermittent dyspnea and no skin involvement. Findings included: non-infectious bronchiolitis and atelectasis signs, biopsy revealed myodystrophal pattern without macrophage infiltration, muscle fiber cytoskeleton disorganization resulted from the plectin loss, incomplete reparative rhabdomyogenesis and moderate endomysial fibrosis. We have determined a novel likely pathogenic variant in PLEC 1f isoform that causes limb-girdle muscle dystrophy type 2Q and described the third case concerning an isolated myodystrophic phenotype of LGMD2Q with the likely pathogenic variant in PLEC 1f isoform. In addition, we have demonstrated the presence of severe lung injury in a patient and his siblings with the same myodystrophic phenotype and discussed the possible role of plectin deficiency in its pathogenesis.